Dataset on the TIC-MOC cruise onboard the R/V Hespérides, March 2015, Brazil-Malvinas Confluence - Orúe Echevarría, Dorleta (2019)
This oceanographic dataset was gathered during the TIC-MOC cruise, which was designed to characterize the dynamics of the Brazil-Malvinas Confluence. The cruise was carried on board the R/V Hespérides, with departure from Ushuaia and arrival to Salvador de Bahía. A total of 66 conductivity-temperature-depth (CTD) stations were completed between 8 and 22 March 2015, offshore from the continental platform and within 45°S-35°S and 61°W-50°W. At each station, water samples were collected, which were used to calibrate the CTD salinity-oxygen sensors and to determine inorganic nutrient concentrations, and the horizontal current was measured. Along its track, the vessel recorded surface temperature and salinity, as well as the horizontal flow down to about 700 m. Lastly, eight position-transmitting drifters were launched and two profiling floats were deployed and later recovered.